PAHLAWAN YANG TERLUPAKAN: PERS MELAYU, ETNIK THIONGHOA, DAN NASIONALISME DI KOTA MALANG 1920-1950 - Reza Hudiyanto (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2007)
In the history of Indonesia, two important events considered to be the turning points of National Awakening were the founding of Budi Utomo ‘Noble Endeavor’ in 1908 and that of Sumpah Pemuda ‘Youth Pledge’ in 1928. The role of young men, external factors and education are considered to be determining factors in the growth of Indonesian nationalism. However, the existence of mass media and colonial sphere also played important roles to swiftly widespread and inculcate new ideas leading to the national awareness as a mass ideology. The role of mass media in accelerating the growth of Indonesian identity from simply an idea into a reality is often underestimated. In fact, one of the many important components on the process of resuscitating national consciousness was vernacular. On the other hand, language was also a component which always imbedded in mass media. Behind the press industry during that era, there must be actors of this activity. Therefore, capital owners also indirectly took part in the growth of Indonesian nationalism.